Tissue characteristics of the athlete"s heart: differentiation of physiological and pathological hypertrophy using parametric T1 and T2 mapping. (8th February 2021) - Vago, H; Dohy, Z; Szabo, L; Czimbalmos, CS; Suhai, FI; Toth, A; Sydo, N; Kiss, O; Csulak, E; Juhasz, V; Hirschberg, K; Becker, D; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Research, Development and Innovation Fund of Hungary Background: Intensive physical exercise leads to structural and functional cardiac adaptation termed athlete's heart. Cardiac magnetic resonance (CMR) has an important role in the differentiation of physiological adaptation and pathological conditions. Beside the precise measurement of the ventricular volumes, mass, and function, it provides tissue specific information. Recently, native T1 mapping technique has been applied as a non-contrast method to detect myocardial fibrosis. Previous studies suggested that native T1 mapping can identify myocardial pathology before other CMR imaging techniques. T2 mapping values are elevated in case of myocardial edema. Purpose: The aim of our study was to investigate the differences in CMR characteristics especially the native T1 and T2 mapping values of highly trained healthy athletes, healthy controls and patients with hypertrophic cardiomyopathy (HCM). Methods: A total of 43 healthy athletes (water polo, swimming, football, 22 ± 8 training hours/week), 27 non-athlete healthy control and 25 HCM patients were involved in the study. Our inclusion criteria were: age >18 years,   in the athlete group >7 training hours per week . We evaluated the left ventricular (LV) end-systolic, end-diastolic (EDVi) and stroke volume (SVi) index, mass index (LVMi), ejection fraction (EF) and maximal end-diastolic wall thickness (EDWT). In a basal short axis slice the native T1 and T2 mapping values were evaluated. Results: Athletes had significantly higher LV volumes compared to the control and HCM group (LVEDVi 114 ± 13 vs. 86 ± 11; 84 ± 15  ml/m2, LVSVi 64 ± 7 vs. 51 ± 7; 54 ± 10 ml/m2, respectively, p < 0.0001). HCM patients had the highest LVMi (72 ± 14 g/m2) and EDWT (18 ± 4 mm) compared to athletes and controls, athletes had higher LVMi (60 ± 11 vs. 42 ± 8 g/m2) and EDWT (10 ± 2 vs. 8 ± 1 mm) compared to the controls (p < 0.001). The native T1 mapping values differed significantly in the three groups, athletes had the lowest, HCM patients had the highest T1 values (athletes: 956 ± 19 ms, controls: 971 ± 20 ms, HCM patients: 993 ± 39 ms; p < 0.0001). There was no difference in the T2 mapping values between athletes and controls (44 ± 2 vs. 43 ± 2 ms), HCM patients had higher T2 values (45 ± 2 ms) compared to the other two groups (p < 0.01). Conclusion: Intensive and regular training may lead to tissue specific changes of the myocardium. T1 and T2 mapping are potentially useful tools for differentiating between athlete"s heart and patients with hypertrophic cardiomyopathy.